(untitled) (قضايا سياسية, 2024)
The cooperative sector is one of the pillars that many countries rely on. The importance of the cooperative sector lies in its ability to become complementary to the public (government) sector, due to its direct impact on the economic and social aspects as a primary source contributing to eliminating unemployment, improving the standard of living, and providing public services to its members in particular and to the society in general. As for the situation in Iraq and what the Iraqi cooperative sector possesses, it would have a profound impact if it takes its natural role. The research aims to identify the extent of the cooperative sector's contribution to the economic, social, and even political advancement of the Iraqi society. The descriptive method was used in the research to study the case. The research concluded the necessity for decision-makers to adopt the cooperative thought within national policies and work on developing cooperative legislation and laws, as well as studying the cooperative reality in Iraq in order to assess and analyze the current situation with the aim of identifying strengths, weaknesses, and available opportunities.